Neighborhood and Individual Socioeconomic Status and Asthma Incidence in African American Women - Coogan, Patricia F. (Ethn Dis, 2016)
OBJECTIVE: Individual socioeconomic status (SES) has been associated with asthma incidence but whether neighborhood SES has an influence is unknown. We assessed the contributions of neighborhood socioeconomic status (SES), neighborhood housing density, neighborhood racial composition, and individual SES to the development of adult-onset asthma in Black women, accounting for other known or suspected risk factors. DESIGN AND PARTICIPANTS: Prospective cohort study conducted among 47,779 African American women followed with biennial health questionnaires from 1995 to 2011. METHODS AND MAIN OUTCOME MEASURES: Incident asthma was defined as new self-report of doctor-diagnosed asthma with concurrent use of asthma medication. We assessed neighborhood SES, indicated by census variables representing income, education, and wealth, and housing density and % African American population, as well as individual SES, indicated by highest education of participant/spouse. Cox proportional hazards models were used to derive multivariable hazard ratios (HRs) and 95% CIs for the association of individual SES and neighborhood variables with asthma incidence. RESULTS: During a 16-year follow-up period, 1520 women reported incident asthma. Neighborhood factors were not associated with asthma incidence after control for individual SES, body mass index, and other factors. Compared with college graduates, the multivariable HR for asthma was 1.13 (95% CI 1.00-1.28) for women with some college education and 1.23 (95% CI 1.05-1.44) for women with no more than a high school education. CONCLUSIONS: Individual SES, but not neighborhood SES or other neighborhood factors, was associated with the incidence of adult-onset asthma in this population of African American women.